The daily rhythms of working memory and their methodological constraints: a critical overview. Issue 7 (3rd July 2022) - Monteiro, Fábio; Rodrigues, Paulo; Nascimento, Carla Sofia; Simões, Fátima; Miguel, Mário
ABSTRACT: Working memory (WM) performance is not constant throughout the 24-hour cycle. Daily oscillations in WM performance are modulated by interactions between circadian and homeostatic factors. However, investigations that ascertained the circadian rhythm(s) of WM found contradictory results regarding the moments in which the lowest and highest peaks of WM performance occur across the light-dark cycle. This review analyses the findings and methodological approaches of past studies that assessed the circadian cycle(s) of WM and explores the main methodological constraints that may explain their mixed findings. Such differences may be explained by (1) the use of diverse experimental protocols; (2) the employment of different degrees of control of confounding exogenous variables; (3) the application of different types of WM paradigms; (4) the use of different conceptualizations and operationalizations to assess the daily rhythm(s) of WM. Some investigations that evaluated the daily pattern of WM performance considered this cognitive function as a single unit and used general/single measures of WM capacity to estimate the parameters of its circadian cycle, while others tried to disentangle the daily rhythms of the subcomponents of WM. Findings of structural and neurobehavioral studies suggest that the subcomponents of WM present independent circadian rhythms.